The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3164/jcbn.20-90
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of Atg5 in intestinal epithelial cells promotes dextran sodium sulfate-induced colitis

Abstract: Autophagy associated genes have been identified as susceptible loci for inflammatory bowel disease. We investigated the role of a core autophagy factor, Atg5, in the development of dextran sodium sulfate (DSS) induced colitis. Intestinal epithelial cell (IEC) specific Atg5 gene deficient mice (Atg5 ΔIEC mice) were generated by cross of Atg5 floxed mice (Atg5 fl/fl) with transgenic mice expressing Cre recombinase driven by the villin promotor. Mice were given three cycles of 1.5% DSS in drinking water for 5 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Further experiments revealed that miR-335-5p exerts biological functions through targeting ATG5. ATG5, an essential autophagosome formation-related protein, modulates various signal pathways like IFN-I, and p53/Rb [ 36 ], and is relative to tumorigenesis and inflammation [ 37 ]. In asthma studies, there is a positive correlation between ATG5 and various collagen gene expression [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments revealed that miR-335-5p exerts biological functions through targeting ATG5. ATG5, an essential autophagosome formation-related protein, modulates various signal pathways like IFN-I, and p53/Rb [ 36 ], and is relative to tumorigenesis and inflammation [ 37 ]. In asthma studies, there is a positive correlation between ATG5 and various collagen gene expression [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…LC3-1 is converted to LC3-2, which is essential in the elongation and closure of the autophagosome membrane for the initiation of autophagy. Nishino et al found DSS-induced colitis was exacerbated in ATG5 deletion mice [ 39 ]. Our results show that the mRNA and relative protein expressions of ATG5, LC3-1, and LC3-2 were increased after LPS challenge, and downregulated by quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…ATG5 is involved in the development of B lymphocytes, as a guardian of immune integrity, in kertain K5 expression in epithelia. This autophagy gene is also important for the prevention of osteoarthritis, cataract, dextran sodium sulfate‐induced colitis and autophagic cell death and in the elimination of mitochondria from embryonic reticulocytes (Morgan‐Bathke et al, 2013 , Honda et al, 2014 , Baerga et al, 2009 , Sukseree et al, 2013 , Ye et al, 2018 , Mizushima et al, 2011 , Miller et al, 2008 , Pyo et al, 2005 , Nishino et al, 2021 ). Deletion of Atg7 has shown a role for this autophagy gene in adipogenesis, hyperglycemia, glucose intolerance, and hypo‐insulinemia, disorders that are common in aging (Bouderlique et al, 2016 , Zhang et al, 2009 , Jung et al, 2008 , Ebato et al, 2008 ).…”
Section: Autophagy Maintains Homeostasis and Restrains Stress Inflamm...mentioning
confidence: 99%